ART LEARNING STRATEGY BASED ON DIRECTIVE INSTRUCTION MODEL - Jagar Lumbantoruan (Fakultas Bahasa dan Seni UNP, 2016)
This article aims to describe the development strategy of art based instruction directive instruction. Learning development strategy is realized through design planning and systematic learning system to solve learning problems. This can be done by adopting relevant learning models. Directive Instruction as a model is done by creating a lesson plan, ie identifying topics, determining learning objectives, and selecting examples and problems. The process of learning planning for a directive instruction model starts from identifying one specific skill desired by educators and learners to be understood and used, formulating specific learning goals that learners are expected to learn, finding and creating high-quality examples that help learners in order to be able to develop a conceptual foundation for the skills that learners will apply later in later examples.Keywords: Strategy, Art Learning, Directive Instruction.STRATEGI PEMBELAJARAN SENI BERBASIS MODEL DIRECTIVE INSTRUCTIONAbstrakArtikel ini bertujuan untuk memaparkan strategi pengembangan pembelajaran seni berbasis directive instruction. Strategi pengembangan pembelajaran diujudkan melalui perencanaan desain dan sistem pembelajaran yang sistematis untuk memecahkan permasalahan pembelajaran. Hal ini dapat dilakukan dengan mengadopsi model pembelajaran yang relevan. Directive Instruction sebagai sebuah model dilakukan dengan membuat rencana pembelajaran, yaitu mengidentifikasi topik, menentukan tujuan belajar, dan memilih contoh dan masalah. Proses perencanaan pembelajaran untuk model directive instruction dimulai dari mengidentifikasi satu keterampilan spesifik yang diinginkan oleh pendidik dan peserta didik untuk dipahami dan digunakan, merumuskan tujuan-tujuan belajar spesfifik yang diharapkan peserta didik untuk dipelajari, menemukan dan membuat contoh-contoh berkualitas tinggi yang membantu peserta didik agar mampu mengembangkan fondasi konseptual bagi keterampilan-keterampilan yang akan diterapkan peserta didik kemudian pada contoh-contoh selanjutnya.Kata Kunci: Strategi, Pembelajaran Seni, Directive Instruction.